Avaliação da acurácia da tomografia computadorizada de feixe cônico no diagnóstico de desadaptação de próteses sobre implante confeccionadas em diferentes materiais - Siqueira, Caíque Araujo (2018)
Introduction: Dental implants are increasingly used after teeth loss to rehabilitate function and aesthetics. A prosthesis is installed over the implant and can be manufactured in several materials. The prosthesis must be well adapted to the implant since misfits may cause an increase in the prosthetic tension values. In order to detect misfits at the prosthesis-implant interface, radiographic and tactile examinations may be used. However, they are susceptible to the operator and the technique used, besides the radiographic examination provides a twodimensional image. Cone beam computed tomography (CBCT) produce three-dimensional images, but studies are lacking to evaluate its performance in the follow-up of implants. Materials with high atomic number and physical density which are used to manufacture implant-supported prostheses may negatively influence the quality of the tomographic image and the diagnosis. Objective: To evaluate the accuracy of CBCT in the detection of misfits at the prosthesis-implant interface with prostheses manufactured in different materials. Material and Methods: 32 external hexagon implants were installed in dried human mandibular jaws. Prostheses of different materials were installed over these implants, constituting 3 experimental groups: porcelain-fused-to-metal, titanium covered by resin, and zirconia covered by ceramics. Misfits were simulated by interposing polyester strips between implant and prostheses. Tomographic images of the mandibles were acquired using the Picasso Trio (85 kVp, 10 mA, FOV 8x5cm and Voxel 0.2mm) with and without the simulated misfits. Five dentists evaluated the images to verify the presence or absence of simulated misfits. The analyses of intra- and inter-reproducibilities were performed using the Kappa test. Descriptive analyses were performed to determine diagnostic values and the values of areas under the ROC curve (Az) were calculated. Results: Intra- and inter-reproducibilities ranged from fair to almost perfect. The highest values of sensitivity, accuracy, positive predictive value and negative predictive value were found for the Titanium group. The largest Az were found for the Titanium (Az = 0.95) and Porcelain-fused-to-metal (Az = 0.90) groups, and the smallest for the Zirconia group (Az = 0.77), with statistically significant differences between Zirconia and Titanium, and Zirconia and Porcelain-fused-to-metal (p <0.05) groups. Conclusion: The detection of misfits at the prosthesis-implant interface through CBCT has a greater accuracy for titanium prostheses coated with resin and porcelain-fused-to-metal.